Metronidazole-induced cerebellar dysfunction: An underdiagnosed identity - Aditya Debuka; Manaswi Chaubey; Shubh N. T. Rai; Ajay Gupta; Jaya Chakravarty (Journal of Family Medicine and Primary Care)
Metronidazole is a commonly used antibiotic in clinical practice. It is associated with neurological toxicity if used for a longer duration or at a higher dose. In our case, the patient was prescribed metronidazole for the treatment of amoebic liver abscess for 7 weeks and he developed metronidazole-induced cerebellar dysfunction and small fibre peripheral neuropathy. Characteristic MRI findings, temporal association of symptoms with drug and resolution on drug withdrawal helped to make the diagnosis. Our case highlights the need of avoidance of prolonged administration of metronidazole and advocates alternative methods including percutaneous drainage to be adopted for a nonresolving liver abscess.